2014
DOI: 10.4161/21624011.2014.955331
|View full text |Cite
|
Sign up to set email alerts
|

Tumor stroma-derived factors skew monocyte to dendritic cell differentiation toward a suppressive CD14+PD-L1+phenotype in prostate cancer

Abstract: Tumor-associated stromal myofibroblasts are essential for the progression and metastatic spread of solid tumors. Corresponding myeloid cell infiltration into primary tumors is a negative prognostic factor in some malignancies. The aim of this study was to define the exact role of stromal myofibroblasts and stromal factors in early prostate carcinoma (PCa) regulating monocyte infiltration and differentiation into dendritic cells (DCs). Epithelial and stromal primary cultures were generated from PCa biopsies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 48 publications
2
52
0
Order By: Relevance
“…Therefore, it appeared that the types of CCR1 + cells were diverse in different tumor microenvironments. Mechanistically, aberrant expression of PD‐L1 was reported to reprogram monocytes toward the immune‐suppressive direction . In this study we showed that, in addition to immune checkpoint, upregulation of immune tolerogenic metabolic enzymes, inflammatory/pro‐antigenic cytokines and matrix remodeling proteases, as well as inflammatory chemokines, may collectively foster the pro‐tumor function of HCC‐infiltrating CCR1 + CD14 + monocytes.…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, it appeared that the types of CCR1 + cells were diverse in different tumor microenvironments. Mechanistically, aberrant expression of PD‐L1 was reported to reprogram monocytes toward the immune‐suppressive direction . In this study we showed that, in addition to immune checkpoint, upregulation of immune tolerogenic metabolic enzymes, inflammatory/pro‐antigenic cytokines and matrix remodeling proteases, as well as inflammatory chemokines, may collectively foster the pro‐tumor function of HCC‐infiltrating CCR1 + CD14 + monocytes.…”
Section: Discussionmentioning
confidence: 64%
“…In order to explore the consequences of STAT3 activation, we inhibited STAT3 phosphorylation with the small molecule inhibitor Cpd188 in cells exposed to sPE, at a concentration we have established previously. 29 Unexpectedly, in the presence of the inhibitor, sPEmediated induction of CD73 expression became significantly enhanced (Fig. 4B).…”
Section: Cd73 Induction On Cd14 C Cells By Spe Is Enhanced By Stat3 Imentioning
confidence: 99%
“…25 Notably, the expression of CD274 (a potent immunosuppressive molecule also known as PD-L1) by MDSCs and other immunosuppressive myeloid cells also depends on STAT3. 26 This latter observation suggests that STAT3 inhibition may downregulate PD-L1, implying that combining AZD9150 with checkpoint blockers 27,28 targeting the interaction between PD-L1 and its main receptor (programmed cell death 1, PDCD1, best known as PD-1) may not be useful. However, this conjecture remains to be investigated at the experimental level.…”
mentioning
confidence: 98%